Interpeduncular heterotopia in Joubert Syndrome: a previously undescribed MR finding - Harting, Inga; Kotzaeridou, Urania; Poretti, A.; Seitz, Angelika; Pietz, Joachim; Bendszus, Martin; Boltshauser, E. (American journal of neuroradiology, 2011)
SUMMARY: The so-called molar tooth sign is the radiologic hallmark of JSRD. Joubert syndrome is a rare, most often autosomal-recessive disorder with a characteristic malformation of the midhindbrain. We describe 3 patients with JSRD and the additional MR finding of tissue resembling heterotopia in the interpeduncular fossa, which in one patient was combined with a more extensive intramesencephalic heterotopia. Interpeduncular heterotopia has not been reported previously, either in the context of JSRD or as a separate entity. This new imaging feature enlarges the spectrum of brain stem abnormalities in JSRD. In view of the underlying ciliopathy, it seems likely that the interpeduncular heterotopia results from misdirected migration.